The dimension of the moduli spaces of curves defined by topologically non quasi-homogeneous functions. (May 2021) - Loubani, Jinan
Abstract: We consider a topological class of a germ of complex analytic function in two variables which does not belong to its jacobian ideal. Such a function is not quasi homogeneous. The 0-level of such a function defines a germ of analytic curve. Proceeding similarly to the homogeneous case Genzmer and Paul (2011) and the quasi homogeneous case Genzmer and Paul (2016), we describe an algorithm which computes the dimension of the generic strata of the local moduli space of curves.